2013
DOI: 10.5455/jib.20121125075314
|View full text |Cite
|
Sign up to set email alerts
|

Serum Lipid Profile of Breast Cancer Patients in Kashmir

Abstract: Malignancy of the breast is one of the commonest causes of death in women aged between 40-45 years. The aim of this study was to carry out a comparative study to investigate the effect of lipid profile, oestradiol (EST) and obesity on the risk of a woman developing breast cancer. In this study, 120 women including 60 breast cancer patients (25 to 80 years) were assessed for lipid profile, EST and Body Mass Index (BMI) and 60 controls with similar age range. There was a significant increase in Body Mass Index (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 21 publications
3
10
1
Order By: Relevance
“…We found increased level of serum TC in both pre and postmenopausal breast cancer patients as compared to their respective control group. Our findings were in accordance to the several other studies [18][19][20][21].An increased level of TC was observed in breast cancer patients on chemotherapy as compared to control but the differences were not statistically significant [9,26].In contrast to our finding, a study by Timovska et al found decreased level of serum total cholesterol after two courses of neoadjuvant chemotherapy [22].In the present study, we observed decreased HDL-cholesterol level in breast cancer patient but the difference was statistically non significant as compared tocontrol group. The previous studies conducted on breast cancer patients reported unchanged or slightly decreased HDLcholesterol level in breast cancer patients as compared to control group [9,20,21].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…We found increased level of serum TC in both pre and postmenopausal breast cancer patients as compared to their respective control group. Our findings were in accordance to the several other studies [18][19][20][21].An increased level of TC was observed in breast cancer patients on chemotherapy as compared to control but the differences were not statistically significant [9,26].In contrast to our finding, a study by Timovska et al found decreased level of serum total cholesterol after two courses of neoadjuvant chemotherapy [22].In the present study, we observed decreased HDL-cholesterol level in breast cancer patient but the difference was statistically non significant as compared tocontrol group. The previous studies conducted on breast cancer patients reported unchanged or slightly decreased HDLcholesterol level in breast cancer patients as compared to control group [9,20,21].…”
Section: Discussionsupporting
confidence: 83%
“…Our findings were in accordance to the several other studies [18][19][20][21].An increased level of TC was observed in breast cancer patients on chemotherapy as compared to control but the differences were not statistically significant [9,26].In contrast to our finding, a study by Timovska et al found decreased level of serum total cholesterol after two courses of neoadjuvant chemotherapy [22].In the present study, we observed decreased HDL-cholesterol level in breast cancer patient but the difference was statistically non significant as compared tocontrol group. The previous studies conducted on breast cancer patients reported unchanged or slightly decreased HDLcholesterol level in breast cancer patients as compared to control group [9,20,21]. A few other studies reported significantly decreased HDL-cholesterol level in breast cancer patients [18,23,26].In contradict to our study; Peela et alfound significantly increased level of HDLcholesterol in breast cancer patients as compared to control [19].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…They found significant increase in BMI, Total Cholesterol, triglyceride and low density lipoprotein (LDL-cholesterol) in the breast cancer patients as compared to the controls. BMI, TC and TG were increased in both pre-menopausal and post menopausal cases with HDL-cholesterol remaining unchanged [16]. Laisupasin et al, studied a total of 403 women.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained by Peela et al, [31], and in a Danish study, demonstrating a statistically insignificant negative correlation between TG and breast cancer. Several other studies demonstrated a significant increase in TG value in patients with breast cancer [22,24,31,32]. Preventing the rise of cholesterol levels, both by limiting its availability and reducing its intracellular synthesis, might inhibit tumour growth and prevent carcinogenesis [33].…”
Section: Discussionmentioning
confidence: 98%